Frailty's Prevalence and the Association with Aging-Related Health Conditions in Chinese Community Dwelling Elderly. (16th August 2022) - Lin, Hongxiao; Wang, Dongyan; Ma, Shanjun; Suo, Yan; Zhou, Peng; Zhao, Qing; Liu, Juan; Ding, Guoxian
Abstract : In this paper, we have investigated the frailty's prevalence and the association with aging-related health conditions in Chinese community dwelling elderly aged ≥60 years in Lianyungang City of China. In this regard, participants were 1, 072 adults aged ≥60 years from Houhe Community of Lianyungang City of China. All the enrolled participants were tested for following parameters: (1) the related risk factors of frailty: including economic status, personal health, understanding and communication skills, and mental and psychological status; (2) aging-related health conditions related to frailty: Charlson's comorbidity index (CCI), Mini Nutritional Assessment Short Form (MNA-SF), Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder 7-item (GAD-7); (3) body composition, physical strength, and function testing: appendicular skeletal muscle mass index (ASMI), grip strength, five-repetition sit-to-stand test, 6 m walking speed, and strength assistance rise-climb-fall (SARC-F); (4) assessment of the degree and severity of frailty: physical frailty phenotype (PFP), Morse fall scale (MFS), and activities of daily living (ADL). The frailty's prevalence among the elderly aged ≥60 years in the community of Lianyungang City was 13.8%, 55.4% were prefrail, and 30.8% were robust. The independent risk factors of frailty were age, appendicular skeletal muscle mass index, sarcopenia, education, nutrition, and strength assistance rise-climb-fall P < 0.05 . Aging-related health conditions were associated with frailty, including sarcopenia, nutrition, and falls. However, mental and psychological statuses were not significantly associated with frailty.